Pre-Service Teachers and Educational Management in Multicultural Schools - เรืองศรี เสาวลักษณ์; สุขประเสริฐ ณรงค์; พันเพ็ชร สุวัฒนวงศ์; บุญญประภา พัฒนา; เดชชวนากร กิตติวินท์ (Community and Social Development Journal, 2019)
This qualitative research aimed to study a form of educational management in multicultural schools of pre-service teachers and techniques used in learning in order to serve differences of learners. This research uses the theory of multicultural study (Banks, J.: 1994) to be scope of research. The main tool for gathering and analyzing information is structured interview of pre-service teachers from program of industrial arts, Faculty of Sciences and Technology, Chiang Mai Rajabhat University, 2nd semester and academic year of 2017 of professional experience in a public school in Chiang Mai and participant observation has been applied by observing the form of learning management of pre-service teachers of educational management in multicultural schools. The finding found that pre-service teacher realized necessary by using techniques for teaching in order to serve differences of learners and be up to date about current news and knowledge. This will help to encourage the interest of learners. The condition of the learning process in multicultural schools about different ability and culture of learners influences the result of learning and the importance of developing curriculum and teaching techniques which are able to help learners to learn as per their abilities and culture in order for the better result of studying.